Criteria for Classification of Risks of Project Financing in Оrder to Manage the Risks of Specialized Lending Portfolio - T. S. Gaibov (Мир новой экономики)
In the article we analyzed international and Russian methodological approaches for classification of risk in project finance and identified crucial criteria which provide further framework for development of principles and management mechanism of specialized credit portfolio at commercial bank. Considering relevant literature and taking into account the main purpose of the study, the practical use of aggregation of project finance risk taxonomy was concluded and three groups of risk were proposed: product risk, counterparty risk and portfolio risk. For each group, it was highlighted list of significant risks all of which shall be subsequently integrated into overall assessment of risks’ concentration of specialized credit portfolio together with some management tools.